2011
DOI: 10.1002/mc.20773
|View full text |Cite
|
Sign up to set email alerts
|

OCT4 spliced variant OCT4B1 is expressed in human colorectal cancer

Abstract: OCT4, a POU-domain transcription factor is considered to be a key factor in maintaining the pluripotency of stem cells. Several OCT4 isoforms are differentially expressed in human pluripotent and non-pluripotent cells. Reactivation of OCT4 expression is postulated to occur in differentiated cells that have undergone tumorigenesis. To examine OCT4 expression in colorectal cancer (CRC) tissues, and to assess the efficacy of OCT4 as a potential biomarker for CRC, in this study, we investigated its expression in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 36 publications
3
43
0
2
Order By: Relevance
“…Notably, the BMP4 pathway is involved in mammalian palatogenesis [71], and mutations in BMP4 have been associated with human NSCL/P [12], [58], [59]. Research has shown that OCT4 is overexpressed in cancer cell lines and in diverse cancer entities [24], [37], [67], suggesting that aberrant transcriptional regulation of OCT4 might be a mechanism in cancer susceptibility. Thus, a plausible hypothesis is that rs6457327 regulates OCT4 expression, and that this regulation is a possible common process in oncogenesis and the development of NSCL/P.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the BMP4 pathway is involved in mammalian palatogenesis [71], and mutations in BMP4 have been associated with human NSCL/P [12], [58], [59]. Research has shown that OCT4 is overexpressed in cancer cell lines and in diverse cancer entities [24], [37], [67], suggesting that aberrant transcriptional regulation of OCT4 might be a mechanism in cancer susceptibility. Thus, a plausible hypothesis is that rs6457327 regulates OCT4 expression, and that this regulation is a possible common process in oncogenesis and the development of NSCL/P.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of OCT4B1 has been related to poor prognosis in cancer in several studies. Expression of OCT4B1 was upregulated in CRC tissues, compared to adjacent non-cancerous tissues, which suggested OCT4B1 to represent a potential biomarker for the initiation, progression and differentiation of CRC (26). Like OCT4B1, SOX2 is reported to act as an oncogene, being upregulated in CRC, and in esophageal squamous cell carcinoma, where it correlated to poor clinical outcome (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of data has showed up-regulation of key stemness factors, like Sox2 and Nanog in several types of cancer cells and the importance of targeting these regulators in cancer therapy (2)(3)(4)(5)(6)(7)(8). Sox2 and Nanog are transcription factors that are essential for maintaining self-renewal or pluripotency of undifferentiated embryonic stem cells (17).…”
Section: Discussionmentioning
confidence: 99%